2023
DOI: 10.1186/s12879-023-08104-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of pneumothorax and pneumomediastinum in COVID-19: a matched case–control study

Abstract: Background During the novel coronavirus disease-2019 pandemic, a considerable number of pneumothorax (PNX)/pneumomediastinum (PNM) associated with COVID-19 have been reported, and the incidence is higher in critically ill patients. Despite using a protective ventilation strategy, PNX/PNM still occurs in patients on invasive mechanical ventilation (IMV). This matched case–control study aims to identify the risk factors and clinical characteristics of PNX/PNM in COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…(24) Similarly, a matched case-control study of 427 patients showed that PTX patients had a lower average BMI (22.4) than non-PTX patients (24.5), which falls under the lower range compared to our population. (25) In contrast, a large study composed of 9800 COVID-19 patients, of which 67 developed PTX, two thirds of the affected patients had a BMI over 25. (26) Due to the con icting evidence, additional research is needed to thoroughly assess the association between COVID-19, PTX, and other comorbidities.…”
Section: Discussionmentioning
confidence: 98%
“…(24) Similarly, a matched case-control study of 427 patients showed that PTX patients had a lower average BMI (22.4) than non-PTX patients (24.5), which falls under the lower range compared to our population. (25) In contrast, a large study composed of 9800 COVID-19 patients, of which 67 developed PTX, two thirds of the affected patients had a BMI over 25. (26) Due to the con icting evidence, additional research is needed to thoroughly assess the association between COVID-19, PTX, and other comorbidities.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, as previously described in spontaneous pneumothorax, a higher BMI seems to be a protective factor in COVID-19-associated pneumothorax. A prolonged time from symptoms onset to intubation has also been associated with an increased risk of pneumothorax [ 6 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, as previously described in spontaneous pneumothorax, a higher BMI seems to be a protective factor in COVID-19-associated pneumothorax. A prolonged time from symptoms onset to intubation has also been associated with an increased risk of pneumothorax [6] . A recent case report described the occurrence of pneumothorax following a severe COVID-19 infection in a previously healthy patient, who was transiently mechanically ventilated.…”
mentioning
confidence: 99%